Incidence and prognosis of critical congenital heart disease in neonates at Charlotte Maxeke Johannesburg Academic Hospital - Mogajane, Tshiamo Paul (My University, 2018)
Background: A significant number of neonates with congenital heart disease present with a life-threatening illness in the neonatal period where survival depends on timely diagnosis, management and referral. Objectives: To determine the incidence and prognosis of critical congenital heart disease in neonates admitted to Charlotte Maxeke Johannesburg Academic Hospital, and to compare it with international data. Method: This was a retrospective, descriptive study of neonates with critical and non-critical congenital heart disease admitted to Charlotte Maxeke Johannesburg Academic Hospital between 01 January 2006 and 31 December 2014. Results: There were 284 neonates diagnosed with congenital heart disease during the study period - 133 with critical congenital heart disease (8.2 per 1000 neonatal admissions) and 151 with non-critical congenital heart disease (9.3 per 1000 neonatal admissions). The mortality rate for neonates with critical congenital heart disease was 61/133 (45.9%). Conclusion: Critical congenital heart disease is not commonly diagnosed in neonates, however the mortality rate is high. Increased awareness and screening programs may improve early diagnosis and allow timeous intervention.
Keywords: Congenital, Hereditary, and Neonatal Diseases and Abnormalities